Dirac operators on compact Riemannian manifolds (2017)
In this monograph we study the algebraic and geometric preliminaries for a Dirac operator and the necessary conditions to define it. We develop in detail the construction of the Dirac operator in the 2-sphere and obtain its spectrum. Finally we show that Connes's distance formula is valid in the unit circle in and the 2-sphere.--Tomado del Formato de Documento de Grado.